Gambaran Kinerja Guru BK Dalam Meningkatkan Sikap Asertif Pada Siswa SMK Korban Bullying - Fitrianingtias, Ika Desy; Hasanah, Nurul (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2023)
Abstract: This study aims to describe and analyze the performance of vocational guidance and counseling teachers from planning, implementing, evaluating and constraining. This type of research method uses behavioral counseling techniques with a case study design. The results showed that; Implementation, almost all planned programs are implemented, there are some that have not been able to run smoothly. Guidance and counseling teachers carry out incidental activities because they prioritize the situation in the field to help deal with students. There are subjects that have not been resolved in instilling an assertive attitude towards their children and students. The response of some students to the guidance and counseling teacher was good, caring, motivating, and educating and there were some students' views who still did not dare to meet the BK teacher. The guidance and counseling room is comfortable and towards the ideal. Obstacles, it is hoped that all obstacles can be resolved properly. Individual counseling for counselees of victims of bullying is a strategy that BK teachers apply to students who are clearly victims of bullying who have low assertiveness skills so that they need to be trained in assertiveness skills. Group guidance/counseling to practice assertiveness in students so that it can help in a wider spectrum, as well as classical guidance to provide information about what assertiveness is, the importance of assertiveness and its application in everyday life. For the counseling process carried out by BK teachers, it is the same as other counseling, individually and in groups.